Association of uric acid with metabolic parameters and obesity. Issue 6 (18th April 2020) - Mahdavi-Roshan, Marjan; Movahedian, Mina; Kord Varkaneh, Hamed; Salari, Arsalan; Sedanur Macit, Melahat; Rezazadeh, Arezoo
Abstract : Purpose: Recent studies have shown that hyperuricemia is a predictor of non-communicable disease and an increment of mortality rate. Also, elevated serum uric acid may be associated with obesity in the adult population. This study aims to evaluate the association between serum uric acid levels with metabolic parameters and risk of obesity in the Iranian population. Design/methodology/approach: The cross-sectional study was done on 550 participants, who were referred to a hospital for elective angiography in Rasht, Iran; anthropometric indices (waist circumference (WC) and body mass index (BMI)) and hematological factors were measured using the standard approaches. Based to the angiography results, the severity of atherosclerosis was defined. Findings: The mean (SD) concentration of serum uric acid for all participants was 5.15 (1.37) mg/dl. Individuals who were at the highest tertile had higher mean (SD) of weight ( p = 0.004), creatinine and blood urea nitrogen ( p < 0.001) lower fasting blood sugar (FBS) ( p = 0.000) and HbA1c ( p = 0.016), and they were mostly men compared with those in the lowest tertile. After adjusting for confounders, FBS ( ß = –0.145, p = 0.001) and HbA1c (%) ( ß = –0.130, p = 0.019) had inverse and weight ( ß = 0.156, p = 0.001) had direct association with serum uric acid. After adjustment for additionally potential confounders subjects in the highest tertile of serum uric acid had 92 per cent higher chance of obesity compared with subjects in the lowest tertile (OR 1.92; 95 per cent CI 1.13, 3.23). Originality/value: The present study has concluded that increase serum uric acid related to high risk of obesity and low mean of FBS and HbA1c.